Resonant Leadership : renewing yourself and connecting with others through mindfulness, hope, and compassion - Boyatzis, Richard E.; McKee, Annie, 1955- (Boston : Harvard Business School Press, 2005)
Leaders everywhere recognized the validity of resonant leadership, but struggled with how to achieve and sustain resonance amid the relentless demands of work and life. Now, the authors provide an indispensable guide to overcoming the vicious cycle of stress, sacrifice, and dissonance that afflicts many leaders. Drawing from extensive multidisciplinary research and real-life stories, this book offers a field-tested framework for creating the resonance that fuels great leadership. Rather than constantly sacrificing themselves to workplace demands, leaders can manage the cycle using specific techniques to combat stress, avoid burnout, and renew themselves physically, mentally, and emotionally. The book reveals that the path to resonance is through mindfulness, hope, and compassion and shows how intentionally employing these qualities creates effective and enduring leadership. Great leaders are resonant leaders. The book offers the inspiration and tools to spark and sustain resonance in ourselves and in those we lead.
Great leaders move us -- The leader's challenge -- Dissonance is the default -- Waking up to resonance and renewal -- Intentional change -- Mindfulness -- Hope -- Compassion -- "Be the change you want to see in the world" -- Power stress, the sacrifice syndrome, and the renewal cycle.
Includes bibliographical references (pages [235]-274) and index.
Description based on print version record.
Keywords: Leadership; Leiderschap; Leadership; Leiderschap; Leadership; SOCIAL SCIENCE / General; elektronické knihy; electronic books